2019
DOI: 10.15171/jcs.2019.005
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Psychometric Testing Persian Version of Breast Cancer Screening Belief Questionnaire (BCSBQ) in Iranian Women

Abstract: Introduction: Women's screening beliefs play an important role in their performance. Since a short form questionnaire is necessary in the assessment of screening beliefs in Iranian society, this study was conducted with the aim of psychometric evaluation of the Breast Cancer Screening Beliefs Questionnaire (BCSBQ) among Iranian women. Methods: In this cross-sectional methodological study, 300 Iranian women who were aged 18 years or older, and who were attending healthcare centers of Shahid Beheshti University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…3 The symptoms of CC normally occur at the advanced stage, leading to the vitiation of the optimum treatment time and high mortality, particularly in developing countries. 4,5 In addition, smoking, age, race and secondary malignancies caused by invasiveness are critical risk factors of poor prognosis. 6 Therefore, the discovery of novel biomarkers is imperative for the therapy of CC.…”
Section: Introductionmentioning
confidence: 99%
“…3 The symptoms of CC normally occur at the advanced stage, leading to the vitiation of the optimum treatment time and high mortality, particularly in developing countries. 4,5 In addition, smoking, age, race and secondary malignancies caused by invasiveness are critical risk factors of poor prognosis. 6 Therefore, the discovery of novel biomarkers is imperative for the therapy of CC.…”
Section: Introductionmentioning
confidence: 99%
“…SaeiGhare Naz ve arkadaşları İranlı kadınlarla yaptıkları çalışmada kadınların rahim ağzı kanseri taraması puan ortalamasını 90.1±14.5 olarak bulmuştur. 26 Bu araştırmada kadınların aynı ölçekten aldıkları puan ortalamasının 93.00±11.5 olduğu belirlenmiştir. Araştırma sonuçları paralellik göstermektedir.…”
Section: Discussionunclassified
“…Kadınların sosyal tutumlarından etkilenen birçok faktör, kadınların serviks kanseri için risk altında olmadıklarına inanmalarına neden olmaktadır. 26 Bu nedenle kadınların serviks kanseri, Papsmear ve çeşitli eğitim müdahaleleri ile ilgili tarama inançlarının belirlenmesi, kadın sağlığının geliştirilmesinde ve serviks kanserine bağlı ölümlerin azaltılmasında önemli rol oynayabileceği düşünülebilir.…”
Section: Discussionunclassified
“…A recent 2018 systemic review by Saei Ghare Naz et al examined 37 articles with 15,658 female participants in different parts of the world to review educational interventions for cervical cancer screening behavior of women. They found that different interventions, such as postcards, consultation sessions, picture books, videos, PowerPoint slides, small group discussions, educational brochures, lecture presentations, and fact sheets, were effective in modifying cervical cancer behavior of women (Saei Ghare Naz et al, 2018). Clinicians would choose the educational materials that best met the needs of their diverse female population.…”
Section: Practice Implicationsmentioning
confidence: 99%